The complete Valley of the Kings : tombs and treasures of Egypt's greatest Pharaohs - Reeves, Carl Nicholas; Wilkinson, Richard H. (London : Thames and Hudson, 2006)
Preparations for the afterlife - Agents of discovery - Tombs of the Kings - Decline of a royalcropolis